Ultrasensitive fluorescence detection of antitumor drug methotrexate based on a terbium-doped silica dendritic probe. Issue 37 (2nd September 2021) - Mohammadzadeh, Arezoo; Jouyban, Abolghasem; Hasanzadeh, Mohammad; Shafiei-Irannejad, Vahid; Soleymani, Jafar
Abstract : A simple fluorescence probe was developed for sensitive detection of methotrexate in biological samples. The developed probe is based on a silica nanocomposite with a biocompatible nature. Abstract : A novel strategy was developed for the detection of methotrexate (MTX) via the quenching effect of MTX on the fluorescence intensity of terbium-doped dendritic silica particles (Tb@KCC-1). The fluorescence intensity of Tb@KCC-1 can be effectively quenched by MTX at 546 nm under an excitation wavelength of 233 nm. The quenched fluorescence is proportional to the amount of MTX in both plasma and exhaled breath condensate (EBC) samples. Under the optimal conditions, the linear dynamic ranges of the developed method were 44 nM to 2.2 μM for EBC, 44 nM to 0.22 μM and 0.22–2.2 μM for plasma samples. The limit of detection (LOD) and limit of quantification (LOQ) in both plasma and EBC media are 35 and 116 nM, respectively. The developed method has the benefits of fast analysis time, simple approach, high specificity, and sensitivity for the detection of MTX in both media. This nanoprobe has been successfully utilized for the quantification of MTX in patients' plasma and spiked EBC samples, proving the applicability of the nanoprobe for MTX detection in real samples.